Clinical benefits of treatment with SQ house dust mite sublingual tablet in house dust mite allergic rhinitis. Issue 10 (11th April 2017) - Demoly, P.; Kleine‐Tebbe, J.; Rehm, D.
Abstract: Treatment with SQ (standardised quality) house dust mite sublingual tablet for 1 year resulted in a decreased probability of having an allergic rhinitis (AR) exacerbation day (from 11% [placebo] to 5% [SQ house dust mite sublingual tablet]) and an increased probability of having a mild AR day (from 16% [placebo] to 34% [SQ house dust mite sublingual tablet]).